The impact of vitamin D status on hungry bone syndrome after surgery for primary hyperparathyroidism. Issue 1 (January 2018) - Kaderli, Reto Martin; Riss, Philipp; Dunkler, Daniela; Pietschmann, Peter; Selberherr, Andreas; Scheuba, Christian; Niederle, Bruno
Abstract : Objective: Prolonged hypocalcemia but normal intact parathyroid hormone (iPTH) levels after surgery for primary hyperparathyroidism (PHPT) are referred to as 'hungry bone syndrome' (HBS). The aim was to evaluate preoperative risk factors for HBS with a focus on the impact of 25-hydroxyvitamin D (25(OH)D) deficiency. Design: Patients having undergone initial successful surgery for sporadic PHPT within 6 years were considered for retrospective analysis. Methods: A total of 385 patients were evaluated, of whom 33 (8.6%) developed HBS influencing negatively the postoperative bone metabolism. All patients underwent biochemical evaluations two days before parathyroid surgery and were followed biochemically on a daily basis in the first postoperative week and thereafter at 8 weeks and 6 months. Conclusions: No relationship was established between preoperative 25(OH)D deficiency and HBS. The only significant risk factor for HBS in multivariable analysis was high levels of preoperative iPTH. As HBS therefore cannot be predicted preoperatively, we recommend a consistent postoperative calcium and vitamin D supplementation to improve the bone metabolism.